2020
DOI: 10.1002/jlb.3ma0520-113r
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-infected alveolar epithelial cells modulate dendritic cell function through the HIF-1α-NOS2 axis

Abstract: Tuberculosis kills more than 1 million people every year, and its control depends on the effective mechanisms of innate immunity, with or without induction of adaptive immune response. We investigated the interaction of type II alveolar epithelial cells (AEC-II) infected by Mycobacterium tuberculosis with dendritic cells (DCs). We hypothesized that the microenvironment generated by this interaction is critical for the early innate response against mycobacteria. We found that AEC-II infected by M. tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 61 publications
1
4
0
13
Order By: Relevance
“…Previous studies have demonstrated that Mtb could enter alveolar and interstitial macrophages, type-ii pneumocytes, endothelial cells and fibroblasts (17,18,21,22). In the present study, it was demonstrated that Mtb could enter goblet cells and ciliated cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have demonstrated that Mtb could enter alveolar and interstitial macrophages, type-ii pneumocytes, endothelial cells and fibroblasts (17,18,21,22). In the present study, it was demonstrated that Mtb could enter goblet cells and ciliated cells.…”
Section: Discussionsupporting
confidence: 68%
“…ERα is strongly expressed in granulomatous tissue of patients with TBTB. it was known from previous studies that Mtb could enter alveolar type ii epithelial cells (21,22). To gain a better understanding in whether Mtb could enter human bronchial epithelial cells, a double-label iF analysis was conducted using an antibody against Mtb combined with antibodies against each of the following markers: p63 (data not shown), ScGB1a1 (data not shown), Muc5ac and FoXJ1, commonly used to identify basal cells, secretory club cells, goblet cells and ciliated cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Their intricate relationship forms a feedback loop: overexpressed HIF-1a in tumor can activate the EGFR/PI3K/AKT pathway, and the activated pathway further induces HIF-1a expression. [31][32][33] We speculated that the activation of this loop contributes to improving epithelial cell activity by upregulating EGFR and accelerating immune cell functions via stimulating inflammatory enzymatic gene NOS2, 34,35 resulting in increased radioresistance of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been recently reported that Mtb-infected AEC-II interacts with and modulates DC function. Mtb-infected AEC-II indirectly induced DC maturation by negatively regulating HIF-1α induced NOS2 and switching DC metabolism ( Rodrigues et al., 2020 ). In addition, beta defensin-2 can be produced by Mtb-infected human AEC-II ( Rivas-Santiago et al., 2005 ) and recruits immature DCs to the infection site by binding to the DC chemokine receptor CCR6 ( Yang et al., 1999 ; Biragyn et al., 2002 ).…”
Section: Interaction With Various Cellsmentioning
confidence: 99%